The Application of Transformative Learning Theory to Online Teaching - Glenn A. Palmer; Lorenzo Bowman (Adult Education Research Conference, 2014)
Transformative learning has emerged as a powerful image for understanding how adults learn (Dirkx, 1998). Mezirow (1991) in explaining his theory of transformative learning, maintained that adults seem to realize personal and professional growth when confronted with dilemmas that challenge their existing views of the world. Transformative educators do not necessarily teach content that is significantly different from other educators. However, they teach the content with a different objective in mind. Transformative educators teach with the aim of consciousness-raising (Freire, 1970), critical reflection (Mezirow, 1995), development (Daloz,1986), or individuation (Boyd & Myers,1988). Many adult educators teaching in the traditional face to face classroom environment have long used one or more of these objectives in their delivery strategies. These strategies include role playing, the sharing of critical incidents or other in class strategies designed to engage students.